2010
DOI: 10.1007/s10840-009-9456-x
|View full text |Cite
|
Sign up to set email alerts
|

Successful transcatheter cryoablation in infants with drug-resistant supraventricular tachycardia: a case series

Abstract: In our series, transcatheter cryoablation was an effective treatment for drug-resistant SVT in infants. We encountered some early nonsustained post-procedure SVT; however, such episodes did not predict procedural failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…There are few reports of transcatheter cryoablation in infants 23 , 24 . In our case, although there was transient atrioventricular block during the procedure, this resolved within minutes.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…There are few reports of transcatheter cryoablation in infants 23 , 24 . In our case, although there was transient atrioventricular block during the procedure, this resolved within minutes.…”
Section: Discussionmentioning
confidence: 59%
“…Cryoablation catheters are currently designed for adults, and when used in infants can be susceptible to technical problems that can be overcome to deliver effective therapy. 23 Cyroablation, however, offers significant benefits over radiofrequency ablation. In an animal study, it has been shown that cryotherapy lesions do not injure the coronary arteries of growing myocardium as is sometimes the case with radiofrequency ablation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TCA has been shown to be effective and reliable in pediatric patients with AV nodal reentrant tachycardia or SVT with accessory pathways [15,16]. However, until 2011, studies of TCA use in neonates and infants remained very limited [17,18]. The only publication on this topic is an international multicenter retrospective [12].…”
Section: Discussionmentioning
confidence: 99%